Exception of Mediation Procedure in Bankruptcy Cases According to Supreme Court Regulation Number 1 Year 2016 - Rr. Putri A Priamsari (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2021)
Mediation in Court is regulated in Supreme Court Regulation Number 1 Year 2016 including the exception. This article aims to examine cases with exception of mediation procedure based on PERMA Number 1 Year 2016 and to identify why Bankruptcy Application in Commercial Court is one of cases with exception. This study finds that PERMA (Supreme Court Regulation) Number 1 Year 2016 exempts cases in Commercial Court, Industrial Relation Court, Objection to the Decision of the Indonesia Competition Commission, Decision of Information Commission and Decision of Consumer Dispute Settlement Agency, Application for Annulment of Arbitration Award, Political Party Dispute, Small Claim Court and Cases with time frame. Bankruptcy Application according to Laws of Bankruptcy in Commercial Court is carried on using speedy procedure, a direct legal remedy to the Supreme Court. Its Application and resolution are within limited time period.